2013
DOI: 10.1155/2013/238035
|View full text |Cite
|
Sign up to set email alerts
|

Combination with Methotrexate and Cyclophosphamide Attenuated Maturation of Dendritic Cells: Inducing Treg Skewing and Th17 SuppressionIn Vivo

Abstract: Immune disorder is considered the main pathogenesis of autoimmune diseases, such as rheumatoid arthritis (RA). The balance of the two special subsets of CD4+T cells, T helper cell 17 (Th17), and Regulator T cell (Treg) is the key factor of maintaining a normal immune response. Dendritic cells (DCs), which are the most powerful antigen-presenting cells, play an important role in regulating the balance of Th17 and Treg. The combination of disease modifying antirheumatic drugs (DMARDs) is an important strategy of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 36 publications
(43 reference statements)
0
19
0
4
Order By: Relevance
“…Immune disorder is supposed to be one of the main pathogenic mechanisms of autoimmune diseases, such as IBD [82] and rheumatoid arthritis (RA) [83] . Probiotics modulate the host-pathogen interactions by effecting on the innate immune responses, which involve the TLR, NF-κB, MAPK, and c-Jun NH2-terminal kinase (JNK) pathways.…”
Section: Molecular Mechanisms Of Probiotics In Gi Diseasesmentioning
confidence: 99%
“…Immune disorder is supposed to be one of the main pathogenic mechanisms of autoimmune diseases, such as IBD [82] and rheumatoid arthritis (RA) [83] . Probiotics modulate the host-pathogen interactions by effecting on the innate immune responses, which involve the TLR, NF-κB, MAPK, and c-Jun NH2-terminal kinase (JNK) pathways.…”
Section: Molecular Mechanisms Of Probiotics In Gi Diseasesmentioning
confidence: 99%
“…In oncologic studies, low‐dose cyclophosphamide has been shown to induce differentiation of Th17 cells and suppression of Treg cells . Opposite effects were seen in an animal experiment when cyclophosphamide was used along with methotrexate . The studies that addressed the effect of therapy on T‐cell subsets in lupus are limited and were not done on a homogenous cohort.…”
Section: Introductionmentioning
confidence: 99%
“…Данные об ýффекте метотрексата на ДК менее однозначны. В ýкспериментальных исследованиях введение овальбумин-иммунизированным мышам метотре-ксата в сочетании с циклофосфамидом ингиби-рует созревание ДК и смещает баланс в сторону уменьшения Th17 и возрастания регуляторных Т-клеток [10]. В то же время, по данным других авторов, метотрексат не подавляет иммуностиму-лирующей активности циркулирующих ДК [26].…”
Section: Discussionunclassified
“…При ýтом имеются основания полагать, что препара-ты, используемые в лечении РА, способны ока-зывать влияние на функции ДК. Так, в ýкспери-ментальных исследованиях на мышах показано, что метотрексат в сочетании с циклофосфамидом подавляет созревание ДК, ингибирует Th17-сти-мулирующую активность и усиливает способ-ность ДК индуцировать генерацию регуляторных Т-клеток [10]. Толерогенный ýффект на ДК про-демонстрирован для глюкокортикоидов [11,12].…”
Section: Introductionunclassified